2014
DOI: 10.3136/fstr.20.671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grape Seed Extracts on the Melanosis and Quality of Pacific White Shrimp (Litopenaeus vannamei) during Iced Storage

Abstract: The aim of this study was to investigate the effect of grape seed extracts (GSE) at different concentrations (0, 7.5 and 15 g/L) on the melanosis formation and quality of Pacific white shrimp during 9 days of iced storage. The melanosis formation was significantly inhibited and sensory quality was significantly improved in shrimp treated by various concentration of GSE, compared with the control. The increase of pH, total volatile basic nitrogen content and the total bacteria amounts of shrimp treated by 7.5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 31 publications
9
32
0
Order By: Relevance
“…According to the Chinese National Shrimp Sanitary Standard (1994), the TVB-N value of fresh shrimp should be <300 mg/100 g. The TVB-N value of shrimp treated by GTE + chitosan coating was 37.9 mg/100 g at the 9th day of storage in ice. The above results agree with those of previous studies which reported that the TVB-N values of Pacific white shrimp treated with ferulic acid, cinnamaldehyde and grape seed extract were significantly decreased (Mu, Chen, Fang, Mao, & Gao, 2012;Nirmal & Benjakul, 2009a;Sun et al, 2014).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…According to the Chinese National Shrimp Sanitary Standard (1994), the TVB-N value of fresh shrimp should be <300 mg/100 g. The TVB-N value of shrimp treated by GTE + chitosan coating was 37.9 mg/100 g at the 9th day of storage in ice. The above results agree with those of previous studies which reported that the TVB-N values of Pacific white shrimp treated with ferulic acid, cinnamaldehyde and grape seed extract were significantly decreased (Mu, Chen, Fang, Mao, & Gao, 2012;Nirmal & Benjakul, 2009a;Sun et al, 2014).…”
Section: Resultssupporting
confidence: 93%
“…The melanosis formation in all treatments was significantly increased during storage in ice (p < 0.05). This result showed that there was rapid loss in visual quality of Pacific white shrimp during storage in ice, which is similar to our previous studies (Fang et al, 2013;Sun et al, 2014). The melanosis formation in Pacific white shrimp treated by chitosan coating, GTE, and GTE + chitosan coating was significantly inhibited (p < 0.05), compared with the control.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Due to the potential health hazards of chemical additives, natural products, especially natural antioxidants and antimicrobial agents, have been intensively examined as safe alternatives to synthetic compounds (Encarnacion, Fagutao, Hirono, Ushio, & Ohshima, 2010;Maqsood, Benjakul, & Shahidi, 2013). Recently, a series of studies conducted on the utilization of natural extracts to delay melanosis formation and extend the shelf life of seafood (Fang, Sun, Huang, & Yuan, 2013;Nirmal & Benjakul, 2011a, 2011cSun, Lv, Yuan, & Fang, 2014).…”
Section: Introductionmentioning
confidence: 98%